INFORMATION ENGINEERING OF ELECTRONIC TEXTBOOKS IN HIGHER EDUCATION - Marina Mikhailovna Konovtsova (Современная наука и инновации, 2022)
The paper discusses the engineering and development of electronic textbook as a tool for training of future specialists. The use of the suggested technology in teaching process of high educational institutions enables successful activity of a learner in electronic learning environment.